USING SHORT SEQUENCE matK GENE AS BARCODE DNA FOR IDENTIFICATION OF DURIO Sp IN TERNATE ISLAND - S. Sundari; Abdu Mas’ud; Estri Laras Arumingtyas; Didik Wahyudi (Jurnal Biosilampari : Jurnal Biologi, 2022)
The Barcode of Life Consortium (CBOL) recommended a standard method for the identification of plant species using matK and rbcL barcoding gene. This study was aimed to evaluate the efficiency of matK DNA barcoding for identification of local durian (Durio sp.) from Ternate Island. Total 15 local durian has been used in this study. Whole genom DNA was isolated by Geneid plant DNA kit and then successfully amplified by the Polymerase Chain Reaction (PCR) technique using specific primer. MatK successfully amplified with 245 bp in length. MatK has sequencing success (71.3%) and relative high of Quality value 20+ (86%). BLAST analysis of the sequence showed that local durian in Ternate are identifies as Durio zibethinus and Neesia malayana with query cover 97%-99%. It could be concluded that matK with short sequence is not efficience for durian identification. The recommended in this studies for using of molecular markers with sequence lengths above 500 bp would be more effective for the identification of cryptic species Durio sp. and other.